THE ASSOCIATION OF CALF CIRCUMFERENCE AND ALL-CAUSE, CARDIOVASCULAR AND CEREBROVASCULAR MORTALITY: RESULTS FROM THE NATIONAL HEALTH AND NUTRITION EXAMINATION SURVEYS. (April 2021) - Huang, Jiayi; Liu, Lin; Chen, Chaolei; Huang, Yuqing; Shen, Geng; Yu, Yuling; Feng, Yingqing
Abstract : Objective: Very limited data is available on the association of all-cause, cardiovascular and cerebrovascular mortality and calf circumference(CC). The objective of this study was to examine the association between CC and all-cause, cardiovascular as well as cerebrovascular mortality. Figure. No caption available. Design and method: The data from the 1999–2006 National Health and Nutritional Examination Surveys (NHANES) was used. A total of 20, 214 individuals aged >= 18 years who had measured CC were selected for this study. CC was defined as the widest point of calf. To investigate the association between CC and all-cause, cardiovascular and cerebrovascular mortality, Cox regression was used in different models. We further stratified the regression models into subgroups and tested for interaction to assess whether the association between CC and mortality was influenced by other covariates. The Kaplan-Meier analysis was conducted to compare the survival between CC and cause-specific mortality. Results: Current study included 20, 214 participants (47.25% were men and the mean age was 45.8 years). In the fully adjusted model, for each 1 cm increment, CC was inversely associated with all-cause mortality (HR = 0.92, 95% CI = 0.90–0.94, P < 0.0001) and cardiovascular mortality (HR = 0.90, 95% CI = 0.84–0.97, P = 0.0056). Meanwhile, the highest quartile of CC had 50% (HR = 0.5, 95%CI = 0.40–0.64, P trend < 0.001) lower risk of all-cause mortality and 57% (HR = 0.43, 95%CI = 0.21–0.88, P trend = 0.045) lower risk of cardiovascular mortality, compared to the lowest quartile of CC. For cerebrovascular mortality, however, no significant association with CC was found. In the subgroup analysis, we found that CC had more potent protective effect on those who with body mass index (BMI) <25 kg/m 2 (all-cause mortality: HR = 0.80, 95%CI = 0.79–0.82, P interaction < 0.0001; cardiovascular mortality: HR = 0.74, 95%CI = 0.70–0.78, P interaction = 0.0005). Conclusions: Our results suggested an independently inverse association between CC and all-cause and cardiovascular mortality. Besides, CC had more significant protective effect on those who with BMI <25 kg/m 2 . However, CC was not associated with cerebrovascular mortality.